Harnessing a Biocatalyst to Bioremediate the Purification of Alkylglycosides - Wahart, Alice J. C.; Dolan, Jonathan P.; Anderson, Simon D.; Cheallaigh, Aisling Ní; Staniland, Jessica; Lima, Marcelo A.; Skidmore, Mark A.; Miller, Gavin J.; Cosgrove, Sebastian C. (Chembiochem : a European journal of chemical biology, 2024)
As the world moves towards net‐zero carbon emissions, the development of sustainable chemical manufacturing processes is essential. Within manufacturing, purification by distillation is often used, however this process is energy intensive and methods that could obviate or reduce its use are desirable. Developed herein is an alternative, oxidative biocatalytic approach that enables purification of alkyl monoglucosides (essential bio‐based surfactant components). Implementing an immobilised engineered alcohol oxidase, a long‐chain alcohol by‐product derived from alkyl monoglucoside synthesis (normally removed by distillation) is selectively oxidised to an aldehyde, conjugated to an amine resin and then removed by simple filtration. This affords recovery of the purified alkyl monoglucoside. The approach lays a blueprint for further development of sustainable alkylglycoside purification using biocatalysis and, importantly, for refining other important chemical feedstocks that currently rely on distillation. Selective enzymatic oxidation of a long‐chain alcohol by‐product with an immobilised alcohol oxidase, followed by subsequent sequestration of the aldehyde with amino resins is shown. The use of solid supported biocatalysts and reagents enabled a two‐step, one‐pot bioremediation of an alkyl monoglucoside, used as a surfactant in several industries.